Global Constitutionalism, Human Rights and Proportionality: Institutionalizing Socratic Contestation - Mattias Kumm (Journal of Constitutional Justice, 2022)
Global Constitutionalists have described and analyzed how with the spread of rights based judicial review after the end of the Cold War proportionality analysis has become a central feature of reasoning about rights. Yet one of the core questions such a practice raises concerns the legal point of such a practice and the role of courts applying such an open ended test. The institutionalization of a rights-based proportionality review shares a number of salient features and puzzles with the practice of contestation that the Socrates of the early Platonic dialogues became famous for. Understanding the point of Socratic contestation, and its role in a democratic polity, is also the key to understanding the point of proportionality-based rights review. When judges decide human or constitutional rights cases within the proportionality framework, they do not primarily interpret authority. They assess reasons. Not surprisingly, they, like Socrates, have been prone to the charge that they offend the values and traditions of the community, when they critically examine and sometimes reject positions held by public authorities and widely endorsed by citizens. Proportionality-based judicial review institutionalizes a right to contest the acts of public authorities and demand a public reasons-based justification. There are four types of pathologies that occasionally infect democratic decision-making, that rights-based proportionality analysis is well suited to identify: first, restrictions based on tradition, convention or preference that are not connected tom plausible policy concerns. Second, restrictions based on reasons relating to “the good”, which are off limits as a reason to justify restrictions of human and constitutional rights. Third, the problem of government hyperbole or ideology. Here government policies are loosely related to legitimate purposes, but they lack a firm and sufficiently concrete base in reality. Fourth, there is the problem of capture of the legislative process by rent seeking interest groups. Socrates was right to insist that the practice of contestation he engaged in deserves the highest praise in a democratic polity. It is equally true that an impartial and independent court engaged in rights-based proportionality review deserves to be embraced as a vital element of liberal constitutional democracy. The right to contest complements the right to vote as a core legal mechanism empowering citizens to participate and ensuring that government is held accountable.
Keywords: 340; global constitutionalism; proportionality; socratic contestation; judicial review; right to justification